KEHAMILAN REMAJA DI FILIPINA: PERSPEKTIF HIFZ AN-NASL TENTANG KEGALALAN STRUKTURAL DAN HUKUM - Abdul Fatah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This article critically examines whether the national legal framework and prevailing social structure in the Philippines align with the principle of protecting future generations as a fundamental objective of law, viewed through the lens of hifz an-nasl. It argues that teenage pregnancy constitutes a concrete indicator of systemic failure in safeguarding future generations and cannot be sufficiently addressed through reproductive health interventions or formal legal reforms alone. The study employs a library research method with a socio-legal approach, drawing on data from 2020-2025 published by the Philippine Statistics Authority, the Commission on Population and Development, the World Health Organization, the United Nations Population Fund, relevant national regulations, and academic literature on socio-economic conditions and child protection. The findings identify structural disparities and weak law enforcement as core determinants of early pregnancy. Poverty, gender inequality, unequal power relations, and limited access to education and reproductive health services generate layered vulnerabilities, including a shift toward child pregnancy that signals the dysfunction of state preventive mechanisms against sexual violence and exploitation. Despite existing legal frameworks, weak implementation and institutional fragmentation reveal a significant policy gap. From a hifz an-nasl perspective, this reflects an intergenerational protection failure with multidimensional consequences. Theoretically, this study contributes by repositioning hifz an-nasl as a normative-critical framework for evaluating contemporary public policies related to child protection and reproductive health.